Isolation of the heterogeneous nuclear RNA-ribonucleoprotein complex (hnRNP): a unique supramolecular assembly. - Choi, Y D (1984)
The packaging of heterogeneous nuclear RNA (hnRNA), the fate of hnRNA in the nucleus, and the conversion of hnRNA to mRNA are believed to occur as the hnRNA transcript is associated with specific proteins to form a ribonucleoprotein complex termed the hnRNP complex. The identity and organization of the protein constituents of the hnRNP have been a matter of considerable controversy. We report here the isolation of the hnRNP complex from vertebrate cell nuclei, employing immunoprecipitation with monoclonal antibodies against the major proteins that are in contact with hnRNA in HeLa cells. Rapid immunoprecipitation from HeLa nucleoplasm with two different monoclonal antibodies to the hnRNP C proteins (41 and 43 kDa) isolates a similar complex that contains proteins and hnRNA of up to approximately equal to 10 kilobases. The major steady-state [35S]methionine-labeled proteins of the isolated complex are of 34 kDa, 36 kDa (A1 and A2), 37 kDa, 38 kDa (B1 and B2), 41 kDa, 43 kDa (C1 and C2), and doublets at 68 kDa and at 120 kDa. Additional proteins from 45 kDa to very high molecular mass are also seen. The major proteins of the complex appear identical by NaDodSO4/polyacrylamide gel electrophoresis to genuine hnRNP proteins--those which become crosslinked by UV light to the hnRNA in vivo. Immunoprecipitation with a different, noncrossreacting monoclonal antibody to the 120-kDa protein isolates an apparently identical complex of proteins that are present at a similar relative stoichiometry. Similar hnRNP complexes are found in rodent and avian cells. Nuclease digestions indicate that RNA plays a role in maintaining the integrity of the structure and that intact RNA of approximately equal to 125 nucleotides is sufficient to hold the complex of proteins together. The coimmunoprecipitation of the hnRNA and of all of the proteins through antibodies against different genuine hnRNP proteins and from divergent species strongly suggests that the hnRNP complex is a unitary structure of consistent, defined, and conserved components.